Private and public sector consensus on priority, pre-competitive wheat research issues - CGIAR Research Program on Wheat (2021)
Public and private sector scientists identified key translational research areas with a high probability of boosting productivity in wheat and other crops that could be researched in ‘precompetitive’ space.